Cigarette smoking significantly increases basal metabolic rate in patients with rheumatoid arthritis. Issue 1 (14th May 2007) - Metsios, G S; Stavropoulos-Kalinoglou, A; Nevill, A M; Douglas, K M J; Koutedakis, Y; Kitas, G D
Abstract : Objective: Basal metabolic rate (BMR) is the most important indicator of human metabolism and its abnormalities have been linked to undesirable health outcomes. Cigarette smoking associates with increased BMR in healthy individuals; it is also related with worse disease outcomes in patients with rheumatoid arthritis (RA), in whom BMR is high due to hypercatabolism caused by systemic inflammation. We aimed to investigate whether smokers with RA demonstrated higher BMR levels than their non-smoking counterparts. Methods: A total of 53 patients with RA (36 female, 17 male, 20 current smokers) were assessed for: BMR (indirect calorimetry), anthropometrical data, fat-free mass (bioelectrical impedance), physical function (health assessment questionnaire; HAQ) and disease activity (disease activity score DAS28 and C reactive protein). Results: RA smokers and non-smokers were not significantly different for age, height, weight, body mass index and fat-free mass. Compared to non-smokers, smokers with RA demonstrated significantly higher BMR (mean (SD) 1513.9 (263.3) vs 1718.1 (209.2) kcal/day; p<0.001) and worse HAQ (1.0 (0.8) vs 1.7 (0.8); p = 0.01). The BMR difference was significantly predicted by the interaction smoking/gender (p = 0.04). BMR was incrementally higher in light, moderate and heavy smokers (p = 0.018), and correlated with the daily number of cigarettes smoked (r = 0.68, p = 0.04). Conclusion: Current cigarette smoking further increases BMR in patients with RA and has a negative impact on patients' self-reported functional status. Education regarding smoking cessation is needed for the RA population.